Valve thrombosis and thrombolytic therapy in modern era: a case report - Aguilar-Molina, Oswaldo E. (2021)
Prosthetic valve thrombosis is a feared complication with an annual incidence ranging between 0.3 to 1.3%. Diagnostic approach is essential for a better prognosis and ultimately determines the chosen therapeutic strategy. Emergent valvular surgery is usually recommended in hemodinamically unstable patients, large thrombus or recurrent embolic episodes. These high-risk conditions are often not the case. Therefore, in many patients the surgical risk is much greater than that of bleeding associated with thrombolytic administration. Ultra-slow infusions have been reported with similar efficacy and lower rates of bleeding complications. We present a case of mitral prosthetic valve thrombosis considered not feasible to surgical management and subsequently treated with an ultra-slow tissue plasminogen activator infusion.